2012
DOI: 10.1016/j.mayocp.2012.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Avanafil for the Treatment of Erectile Dysfunction: A Multicenter, Randomized, Double-Blind Study in Men With Diabetes Mellitus

Abstract: clinicaltrials.gov Identifier NCT00809471.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 34 publications
7
64
0
4
Order By: Relevance
“…Present data were confirmed by Belkoff et al [25] in a 52-week, open-label extension of two placebo-controlled RCTs [15,20] including 712 subjects with or without diabetes. All patients in this preplanned extension trial were initially assigned to treatment with avanafil 100 mg.…”
Section: Results Evaluationsupporting
confidence: 74%
See 3 more Smart Citations
“…Present data were confirmed by Belkoff et al [25] in a 52-week, open-label extension of two placebo-controlled RCTs [15,20] including 712 subjects with or without diabetes. All patients in this preplanned extension trial were initially assigned to treatment with avanafil 100 mg.…”
Section: Results Evaluationsupporting
confidence: 74%
“…The authors reported data of four placebo-controlled RCTs, [19][20][21] showing that avanafil was superior to placebo in improving vaginal penetration and successful intercourse. [18] However, in that study only a comparison of avanafil 100 mg versus placebo was considered.…”
Section: Clinical Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies were excluded from the final analysis as they did not fulfill inclusion criteria. One RCT was excluded from the analysis as it studied the efficacy and safety of a new PDE5i (Avanafil) in diabetic patients, but it did not analyze endothelial function (39). Two RCTs were excluded as they provided an evaluation of endothelial function after acute rather than chronic treatment with a PDE5i and because of quasi-randomization (40,41).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%